SUCCESSION AND URBANIZATION OF THE EARTH - Hanadi Ail Mohamd Johaifah (Miasto Przyszłości, 2024)
The terms "disagreement" and "modernization" had certain cultural and humanitarian concepts and connotations that might differ from the principles shared by believers and others, and were fundamental principles to be disseminated among them. This problem has been reflected in the attitude and suspension of nations, as well as in their physical and cultural pattern and in their human and cosmic existence and efforts in this regard, This paper strives to shed light and attention on a range of terminology in this area. by its legitimate consideration, as well as by its manifestation of negligence in historical circulation and intellectual business, focusing on the notion of Sunni and values and their vital role.